ANALISIS PENGARUH STRUKTUR MODAL DAN PERPUTARAN MODAL KERJA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT PADA BURSA EFEK INDONESIA - Muh. Yasin Noor W.K (AkMen JURNAL ILMIAH, 2017)
This research is aimed to: (1) test the effect of capital structure for manufacturing value of the firm which registered in Indonesia Stock Exchange (ISE); (2) test the effect of working capital turnover for manufacturing companies which registered in Indonesia Stock Exchange (ISE) ;(3) test both the effect of capital structure and working capital turnover for manufacturing companies which registered in Indonesia Stock Exchange (ISE). This research is a qualitative research with numerical data, such as financial report, explanation of the financial report, etc. The data source is secondary data in written form. The sample establishment is based on purposive sampling method and listed from 2007 until 2009. The data is analyzed with Software SPSS Program series 16.0. The research results show that: (1) capital structure and working capital turnover have a positive and significant effect for the value of the firm; (2) partially, working capital turnover has a negative effect which is in significant to the value of the firm; (3) partially, working capital turnover has a positive and significant effect for the value of the firm.